Kemampuan Bakteri Asam Laktat Dalam Menghambat Pertumbuhan dan Produksi Aflatoksin B2 Aspergilllus flavus - Lunggani, Arina Tri (Bioma : Berkala Ilmiah Biologi, 2007)
Aflatoxins are highly toxic secondary metabolies produced during the growth of several fungi, especiallyAspergillus flavus. AFB1 and AFB2 one of them which contaminates a wide variety of food and feed causing serioushealth problem when consumed by human or animals. This research was aimed to study the potency of Lactic AcidBacteria (LAB) in the inhibition of Aspergillus flavus growth and the production of Aflatoxin B2. Three species ofLAB i.e. Lactobacillus delbrueckii , L. fermentum, L. plantarum were investigated for their potential in inhibitingand degradation of Aflatoxin B2 as well as inhibiting fungal growth. The trial was designed into three variations ofeach isolate by challenging the fungal culture, before fungal inoculation, at the same time as fungal inoculation andafter fungal inoculation. It was found that all the three species of LAB are potential microorganism to inhibitfungal growth as indicated by the reduction of the dry weight of fungal mycelia compared with control.Quantification of Aflatoxin B2 showed that L. fermentum gave the strongest degradation of Aflatoxin B1 during 15days incubation, then followed by L. plantarum and L delbruekii with a reduction rate of 0,,2408 ppm, 0,3373 ppm,0,6393 ppm respectively, compared with control these are significantly different. These result conclude thatAflatoxin B2 can be degraded or prevented to be produced by A. flavus by applying LAB.